2021
DOI: 10.3145/epi.2021.may.08
|View full text |Cite
|
Sign up to set email alerts
|

Communication policies for innovation financed with public funds in Spain: the experts’ view

Abstract: Companies that receive public funds for research and development and technological innovation (R&D&I) projects must comply with certain communication obligations in accordance with relevant Spanish and European laws. The aim of this work is to assess these requirements (including their advantages and limitations) based on the opinion of experts in the field. Interviews were conducted with R&D&I managers in national and regional agencies; innovation, transparency, and scientific dissemination sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…For this reason, the Independent Authority for Fiscal Responsibility [61] proposes the publication of a list of the entities benefiting from R&D&I tax incentives, in order to bring the publicity requirements into line with those for direct aid. Along the same lines, Vilaplana-Aparicio et al [5] also highlight the need to promote transparency measures in R&D&I tax incentives, such as the publication of aggregated data that allow the scope of this aid to be known.…”
Section: The Regulation Of Communication and Transparency In Spainmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, the Independent Authority for Fiscal Responsibility [61] proposes the publication of a list of the entities benefiting from R&D&I tax incentives, in order to bring the publicity requirements into line with those for direct aid. Along the same lines, Vilaplana-Aparicio et al [5] also highlight the need to promote transparency measures in R&D&I tax incentives, such as the publication of aggregated data that allow the scope of this aid to be known.…”
Section: The Regulation Of Communication and Transparency In Spainmentioning
confidence: 99%
“…The academic sphere has also studied compliance with communication and transparency measures in Spain. Studies related to compliance with communication measures highlight the need to homogenise and update the texts of the regulations and the calls for R&D&I grants themselves [1,64]; the underutilisation of online media in the communication process and the disparity in the publication of content by companies [3]; the need to carry out communication plans with a strategy and a detailed action plan before starting subsidised projects [4]; or the need to adapt media and formats to reach the target audience and enhance the impact of dissemination [5]. With regard to transparency, several authors have shown that, despite the evolution experienced in Spain, there are still shortcomings in its implementation [52,65,66].…”
Section: The Regulation Of Communication and Transparency In Spainmentioning
confidence: 99%
See 1 more Smart Citation